2012
DOI: 10.1530/erc-11-0392
|View full text |Cite
|
Sign up to set email alerts
|

The risk of metachronous cancers in patients with small-intestinal carcinoid tumors: a US population-based study

Abstract: Small-intestinal carcinoids (SIC) are the most common small-bowel malignancies. We sought to determine the risk of developing SIC before and after other primary malignancies (PM) and the prognosis of patients with SIC, with and without another PM. We used the Surveillance, Epidemiology, and End Results database to identify patients diagnosed with SICs between 1973 and 2007. Multiple primary-standardized incidence ratios were calculated as an approximation of relative risk (RR) to explore the association of SIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 17 publications
3
22
1
Order By: Relevance
“…Interestingly, they found an increased risk of metachronous SPMs in NET patients in a Taiwanese cohort. Similarly, a study using data from the Surveillance, Epidemiology, and End-Results (SEER) Program found an increased risk of developing metachronous second cancer after a diagnosis of small intestinal carcinoid [16]. These findings conflict with the findings of our study.…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, they found an increased risk of metachronous SPMs in NET patients in a Taiwanese cohort. Similarly, a study using data from the Surveillance, Epidemiology, and End-Results (SEER) Program found an increased risk of developing metachronous second cancer after a diagnosis of small intestinal carcinoid [16]. These findings conflict with the findings of our study.…”
Section: Discussioncontrasting
confidence: 99%
“…Carcinoids are rare neuroendocrine tumors; 67% occur in the gastrointestinal tract, primarily in the small intestine (Amin et al 2012; Kharazmi et al 2013) (Modlin, et al 2003). Carcinoid tumors of the small intestine, presently called small intestinal neuroendocrine tumors (SI-NETs) derive from enterochromaffin cells of the neuroendocrine system in the gut and during development, originate from the same stem cells as the rest of the gut epithelium (not neural crest).…”
Section: Introductionmentioning
confidence: 99%
“…These cells contain a large amount of the body’s store of serotonin and, in response to stimuli in the lumen (chemical, mechanical, pathological), the release of serotonin regulates gut motility and secretion as well as triggering nausea signals to the brain. SI-NETs comprise approximately 40% of all small intestinal primary tumors and are similar in frequency to adenocarcinomas of the small intestine (Amin et al 2012; Kharazmi et al 2013). Incidence of SI-NETS is 0.9 per 100,000 population per year with the rate steadily increasing over the past 30 years (Amin et al 2012; Kharazmi et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations